Flashcards Integrating Musi Banyuasin Local Wisdom for Teaching Addition in Grade I Elementary Schools: A Needs Analysis - Aswandari, Aswandari; Maharani, Siti Dewi; Susanti, Rahmi (Papanda Publisher, 2025)
Mathematics learning in elementary grades faces significant challenges, particularly in teaching addition concepts that students perceive as abstract and disconnected from their cultural experiences. The limited availability of engaging, culturally-relevant learning media leads to reduced motivation and suboptimal understanding of fundamental mathematical concepts. This study aimed to analyze the needs for developing innovative flashcards based on Musi Banyuasin local wisdom as teaching media for addition concepts in first-grade elementary schools. A descriptive survey design was employed involving 23 first-grade students and one classroom teacher at SDN 6 Ngulak, South Sumatra. Data collection utilized structured questionnaires examining six dimensions (pedagogical, technical, cognitive, aesthetic, sociocultural, and evaluation) and semi-structured teacher interviews. Quantitative data were analyzed using descriptive statistics with percentage calculations, while qualitative data underwent thematic analysis to identify implementation requirements and stakeholder perspectives. Student responses demonstrated overwhelming support for innovative flashcard media, with unanimous agreement (100%) on aesthetic and sociocultural dimensions, indicating strong preference for visually appealing materials incorporating familiar cultural elements. High support was also recorded for pedagogical (84.06%) and cognitive aspects (84.78%), while technical dimensions achieved moderate acceptance (63.04%). Teacher interviews corroborated student preferences and identified specific needs for interactive, visual-based learning materials integrating local wisdom elements such as regional fruits from Musi Banyuasin culture. The findings validate the integration of local wisdom in mathematics education, supporting Vygotsky's sociocultural theory and Mayer's multimedia learning principles. Results demonstrate that culturally-responsive flashcard media can effectively bridge abstract mathematical concepts with students' experiential knowledge while addressing contemporary educational challenges in resource-constrained environments.